Socio-Ecological Vulnerability of Forest Dependent Communities to Climate Change along an Altitude Gradient in Western Himalayas - Jha, Shashidhar Kumar; Negi, Ajeet K. (Indian Forester, 2021)
Micro level socio-ecological vulnerability assessment to climate change has a paramount significance in defining climate-risks, identification of site-specific sectoral remedial measures and fabrication of adaptation actions. Cross-sectional survey research design has been employed to examine the extent of socio-ecological vulnerability of 492 randomly selected households in 62 villages along an attitudinal gradient (<1200 m asl (zone A), 1201-1800 m asl (zone B), and >1801 m asl (zone C)) in Pauri District, Uttarakhand. Among the socio-ecological systems, highest vulnerability was recorded in socio-economic sector (0.92) followed by forests (0.80). The vulnerability was directly proportional to elevation and recorded highest in Zone ’C’ (0.80). Socio-ecological systems contribute differently to overall vulnerability and it is determined by systems’ sensitivity and adaptive capacity. Strategies for sector and site-specific adaptation are required that address bottlenecks in availability and accessibility to biophysical resources and socio-cultural complexities in mountainous settings. The results extend current knowledge among the research community and policymakers on socio-ecological changes affecting forest dependent communities. To reduce the policy level gap between bottom-up and top-down approaches, authors suggest precautionary and ongoing site-specific assessment, leading to effective and efficient handling of local issues in the context of climate change.